War in Ippeisotsu’s by Katai Tayama - Ramadhani, Ahmad Fikri; Purba, Esther Risma (Universitas Pendidikan Indonesia (Indonesia University of Education), 2021)
The main objective of this research is to analyze the binary opposition contained in Ippeisotsu’s short story to reveal hidden meanings and provide new meanings about the Japan-Russia war of 1904-1905 by using the Jacques Derrida’s deconstructive reading method. This study also connects the context outside the text, namely the historical context to find the position of the work in the midst of the war situation in 1908. Therefore, Michel Foucault’s theory of power regarding discourse is used to see how the discourse related to war, the image of the ideal army, the doctrine of state defense and obedience to the emperor was constructed. Deconstructive reading method will be used to deconstruct the binary opposition found and then describe it by using qualitative descriptive method. The result of this study is there are six binary oppositions found in Ippeisotsu’s short story. These six binary oppositions are used to reveal hidden meanings and to give new meaning to the Japan-Russia war of 1904-1905. The six binary oppositions found are superior (Japan) and inferior (China), leader and follower, subject of command and object of command, brave soldier and fearful soldier, physically strong soldier and physically weak soldier, and the last is the battlefield and civilian life. If this binary opposition is related to aspects outside the text, namely connecting literary works with wartime situations, then the result of the meaning that is revealed in Ippeisotsu’s short story is a critique of the Japan-Russia war.